ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP POLA ASUH IBU BALITA DI KABUPATEN BANYUMAS (Studi di Puskesmas Banyumas dan Puskesmas II Kembaran) - Dimas Setio Kusuma Aji; Erna Kusumawati; Setiyowati Rahardjo (Kesmas Indonesia, 2016)
Maternal parenting plays an important role in determining the nutritional status of children, when parenting less well in terms of feeding, health care and stimulation of development, can affect the growth and development of children. The purpose of this research is to determine factors that influence parenting mothers in Banyumas district. This type of research is observational analytic with cross sectional design approach. Number 97 children of samples (0-59 months) are taken proportionally by cluster random sampling while the respondents is children’s mother. The data collection used structure interview with questionnaires. Data analysis used univariate (frequency distribution), bivariate (chi-square) and multivariate (logistic regression). The results showed an association between knowledge (p=0.000) and attitude (p=0.000) with the mother's parenting. The results of multivariate showed knowledge and attitudes affect maternal parenting together, while knowledge is the most dominant factor that influence the mother's parenting. Effort to increase maternal parenting behavior that is held guidance in the form of training to midwife and cadres in order to enhance the skills and capabilities of counseling to the community to be able to deliver better information on nutrition and maternal parenting.